The rare and unusual presentation of a gastric perforation in the setting of a large diaphragmatic hernia: a case report and literature review - Lim, Daniel (J Surg Case Rep, 2018)
Diaphragmatic hernias are either congenital or acquired defects in the diaphragm that permit passing of abdominal contents into the chest cavity. Individuals with large diaphragmatic hernias associated with a gastric perforation have rarely been reported in literature and can have serious mortality rates. Herein, we present a case of gastric perforation in the setting of a significant sized diaphragmatic hernia. The value of the current report compared to previously published cases is the sub-acute nature and lack of any indicative features on initial presentation which can lead to misdiagnosis and serious morbidity later in life.